Efficacy, Safety and Long-term Outcomes of Nicorandil Use in Patients with Stable Ischemic Heart Disease According to the Results of Randomized and Observational Studies - Yu. V. Lukina; N. P. Kutishenko; S. Yu. Martsevich (Столичная издательская компания, 2019)
Working Group of the NIKEA Study. Yekaterinburg: Akulina E.N., Reznik I.I.; Izhevsk: Grebnev S.A., Yezhov A., Shinkareva S.E.; Krasnodar: Kudryashov E.A., Skibitsky A.V., Skibitsky V.V., Fendrikova A.V.; Krasnoyarsk: Altayev V.D., Matyushin G.V., Nemik D.B., Pitaev R.R., Samokhvalov E.V., Stolbikov Yu.Yu.; Moscow: Balashov I.S., Voronina V.P., Gaisenok O.V., Dmitrieva N.A., Zagrebelny A.V., Zakharova A.V., Zelenova T.I., Kolganova E.V., Leonov A.S., Lerman O.V., Maximova M.A., Sladkova T.A., Shestakova G.N.; Novosibirsk: Kuimov A.D., Shurkevich A.A.; Omsk: Goodilin V.A., Loginova E.N., Nechaeva G.I.; Orel: Zhuravleva L.L., Lobanova G.N., Luneva M.M., Mitroshina T.N.; Orenburg: Kondratenko V.Yu., Libis R.A.; Rostov-on-Don: Dubishcheva N.F., Kalacheva N.M., Kolomatskaya O.E., Romadina G., Skarzhinskaya N.S., Chesnikova A.I., Chugunova I.B.; Ryazan: Dobrynina N.V., Nikolaev A.S., Trofimova Ya.M., Yakushin S.S.; Tula: Berberfish L.D., Gomova T.A., Gorina G.I., Dabizha V.G., Zubareva L.A., Nadezhkina K.N., Nikitina V.F., Renko I.E., Soin I.A., Yunusova K.N.Background. Nicorandil is an antianginal drug for which, the ability to positively influence the prognosis of patients (pts) with stable ischemic heart disease (IHD) was confirmed in a randomized controlled trial (RCT) of IONA (the Impact Of Nicorandil in Angina). To study whether the results of RCTs are reproduced in real clinical practice seems to be an actual scientific and practical task.Aim. To compare the data on the effectiveness and safety of nicorandil in pts with stable IHD obtained in the NIKEA observational study (OS) and in the IONA randomized study.Material and methods. 590 pts with IHD and stable angina pectoris were included in the OS NIKEA. All pts were recommended to take nicorandil in addition to the standard antiischemic therapy. 21 months after being included in the study, 524 pts received a phone call. During the telephone contact with pts or their relatives, the life status of pts was determined. According to these results of the survey data were obtained, that 15 people died and 509 pts were alive. The events included in the primary combined endpoint (PCEP) were also determined: death from all causes, new cases of acute myocardial infarction and acute cerebrovascular accident, unscheduled operations of myocardial revascularization, hospitalization for decompensation of chronic heart failure, atrial fibrillation, unstable angina, information on taking nicorandil and other drug therapy, adverse events of drug treatment have been reported. A comparative analysis of the results of the OS NIKEA and RCT IONA was carried out. The results of the IONA study were taken according to the publication in the Lancet 2002. A comparative analysis of the results of the effectiveness of nicorandil in real practice (according to the OS results) was performed with the data obtained in the RCT: the nicorandil/placebo groups in the RCT were compared with the adherent/non-adherent nicorandil groups in the OS.Results. The follow-up duration in both studies was similar and averaged 1.6±0.5 years at RCT IONA and 1.8±0.4 years at NIKEA study. The average age of pts was 67,0±8,0 years in RCT and 65.1±9.6 years in OS. In pts of OS more pronounced comorbidity was noted (cardiovascular diseases, diabetes mellitus). Drugs that favorably affect the prognosis in pts with IHD were more often prescribed to NIKEA study pts (p<0.05). In both RCTs and OS, the antianginal effectiveness of nicorandil was confirmed. According to the OS results, a reduction in the number of angina attacks and a decrease in the need for short-acting nitrates were demonstrated. The frequency of PCEP components was higher in RCT.Conclusion. Long-term outcomes according to the NIKEA observational program for various components of the PCEP turned out to be similar to the results of RCT IONA. It is demonstrated the efficacy of nicorandil in real clinical practice.